Covalent functionalization of single-walled carbon nanotubes with polytyrosine: Characterization and analytical applications for the sensitive quantification of polyphenols - Eguílaz Rubio, Marcos (2016)
This work reports the synthesis and characterization of single-walled carbon nanotubes (SWCNT) covalently functionalized with polytyrosine (Polytyr); the critical analysis of the experimental conditions to obtain the efficient dispersion of the modified carbon nanotubes; and the analytical performance of glassy carbon electrodes (GCE) modified with the dispersion (GCE/SWCNT-Polytyr) for the highly sensitive quantification of polyphenols. Under the optimal conditions, the calibration plot for the amperometric response of gallic acid (GA) shows a linear range between 5.0 × 10−7 and 1.7 × 10−4 M, with a sensitivity of (518 ± 5) m AM−1 cm−2, and a detection limit of 8.8 nM. The proposed sensor was successfully used for the determination of total polyphenolic content in tea extracts.